Electrical capacitance tomography: A review on portable ECT system and hardware design - Abd Rashid, Wan Norhisyam; Mohamad, Elmy Johana; Abdul Rahim, Ruzairi; Abdullah, Jaafar; Mohmad Ameran, Hanis Liyana (Emerald Group Publishing Limited, 2016)
Purpose – There are demands from the industry to have a modern application of Electrical Capacitance Tomography (ECT) system which is mobile and agile. One of the factors why such system is needed in the industry is because of the requirement to install the measurement sensors in a hostile and harsh environment which demands a special kind of ECT system. This paper will discuss the features of mobile or portable ECT which is more practical to be implemented in the harsh environment. Besides, the implementation of cloud computing and wireless technology in the portable ECT systems is also discussed. This review outlines some key features of portable or in another word mobile ECT as a complete system. Design/methodology/approach – There are demands from the industry to have a modern application of ECT system which is mobile and agile. One of the factors why such system is needed in the industry is due to the requirement to install the measurement sensors in hostile and harsh environment which demands a special kind of ECT systems. This paper will discuss the features of mobile or portable ECT which is more practical to be implemented in the harsh environment. Besides, the implementation of cloud computing and wireless technology in the portable ECT systems is also being discussed. This review outlines some key features of portable or in another word mobile ECT as a complete system. Findings – This review outlines some key features of portable or in another word mobile ECT as a complete system. A lot of improvement can be done to realize a reliable and stable ECT system. It is seems that in the near future, machine to machine communication will become the main stream. Originality/value – This paper fulfils an identified need to study improvement that can be done to develop a portable ECT system which is reliable and stable. Besides, the implementation of cloud computing and wireless technology in the portable ECT systems is also discussed.